High output impedance current-mode universal filter employing dual-output current-controlled conveyors and grounded capacitors - Tangsrirat, Worapong; Surakampontorn, Wanlop (My University, 2007)
A novel current-controlled two-input three-output current-mode universal filter, which employs only three dual-output controlled-controlled current conveyors (DOCCCIIs) and two grounded capacitors, is presented in this paper. The proposed configuration provides inverting-type lowpass, noninverting-type lowpass, inverting-type bandpass, noninverting-type bandpass, highpass, bandstop and allpass current responses at a high impedance terminal, which enable easy cascadability. The filter also offers an independent electronic control of the natural frequency ωo and the parameter ωo / Q through adjusting the bias current of the DOCCCII. No critical matching condition is required for realizing all the filter responses, and all the incremental parameter sensitivities are low. The performances of the proposed circuit are simulated with PSPICE to confirm the presented theory. © 2006 Elsevier GmbH. All rights reserved.
Keywords: Current-controlled conveyor; Current-mode circuits; Universal filter